PRODUKSI ENZIM SELULASE MELALUI FERMENTASI FASE PADAT PADA KULIT KACANG TANAH (ARACHIS HYPOGEA) MENGGUNAKAN TRICHODERMA SP. DAN RAGI TEMPE - Dhiffah Nabilah Abdul, Sitti
Groundnut (Arachis Hypogea) is one of the superior commodities that are widely cultivated in Indonesia. However, groundnut shell is commonly thrown away as waste. Meanwhile, groundnut shell includes as a lignocellulosic biomass which has the potential as a fermentation substrate for cellulase enzyme production. Cellulase enzyme production through solid state fermentation using fungi can yield higher enzyme activity due to favorable fermentation conditions for fungi. This study aimed to determine optimum fermentation time of groundnut shell using Trichoderma sp. and tempeh yeast to produce cellulase with a high activity. Solid state fermentation was carried out for 1. 2, 3, 4,5 days at room temperature (25 °C). Cellulase activity produced during the fermentation were 0.053 ± 0.011, 0.053 ± 0.001, 0.078 ± 0.003, 0.102 ± 0.006, and 0.051 ± 0.005 FPU/ml, respectively. Furthermore, mathematical model was also simulated using secondary data of solid-state fermentation to determine the kinetic parameters. The model fits well with secondary data (R2 = 0.93-0.99). The value of estimated parameters ?????, Ks, kd, ms, ????????/????, ????????, k1, dan k2 were 1.90 h-1, 4.49 g/g, 0.22 h-1, 0.00007 h-1, 18.26 mg/g, 0.0016 (g/g), 7.0016 U/g.h, and 0.0706 h-1.